2009
DOI: 10.1177/1359105308097948
|View full text |Cite
|
Sign up to set email alerts
|

HIV/STI Risk Communication

Abstract: Health risk judgments are not merely based on risk statistics but also on the ease with which hypothetical events are imagined. We explored the effects of scenario information as opposed to frequency information on susceptibility perceptions regarding Chlamydia and HIV. Results showed that participants felt more susceptible to Chlamydia after reading frequency information. Scenario information only seemed to affect feelings of susceptibility in participants with no intimate relationship. No effects on perceive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(31 citation statements)
references
References 35 publications
1
28
2
Order By: Relevance
“…Based on the literature (e.g., Mevissen et al, 2009;De Wit et al, 2008), we expected a medium effect size on primary outcomes (η2 = .06 ;Cohen, 1988). In our design with 2 means per factor, this effect size value corresponds to a d-value of 0.50, and an f-value of 0.25.…”
Section: Required Sample Sizementioning
confidence: 99%
See 2 more Smart Citations
“…Based on the literature (e.g., Mevissen et al, 2009;De Wit et al, 2008), we expected a medium effect size on primary outcomes (η2 = .06 ;Cohen, 1988). In our design with 2 means per factor, this effect size value corresponds to a d-value of 0.50, and an f-value of 0.25.…”
Section: Required Sample Sizementioning
confidence: 99%
“…Moderating factors. Comprehensibility was assessed by a composite of three items accounting for the extent to which mothers understood the information, and whether they considered the text to be clear and readable (Mevissen et al, 2009). Responses were given on a seven-point scale ranging from (1) not at all understandable/very unclear/very readable to (7) fully understandable/very clear/very readable (Cronbach's alpha = .87).…”
Section: Measurementsmentioning
confidence: 99%
See 1 more Smart Citation
“… A action stage of change, P preparation for action stage of change, C contemplation stage of change, CRC colorectal cancer, CRCS colorectal cancer screening, PC precontemplation stage of change, TTM trans-theoretical model a Processes of change are from Prochaska et al [58] b Techniques of change are from Michie et al [59] c Techniques of change are from Mevissen et al [60] d Techniques of change are from Suls et al [61] …”
Section: Figmentioning
confidence: 99%
“…The results showed that providing young adults with risk scenario information indeed led to higher perceived susceptibility for Chlamydia (Mevissen et al, 2009). However, the influence of scenario information on Chlamydia-related susceptibility perceptions depended on the relationship status of the recipient: only among participants without a steady relationship at time of measurement, perceived susceptibility was rated higher after reading scenario information compared to not reading scenario information.…”
Section: The Impact Of Scenario Information On Chlamydia Risk Perceptmentioning
confidence: 90%